WHAT DO WE LEARN FROM LITERATURE - Hartono, Hartono (Jurnal Bestari, 1992)
It is quite evident that most of us are indifferent to literature. To illustrate, let me just quote some people?s comments on the works. ?I do not understand what the importance of literature to our life is. For me, personally, literature does not have any influence on my life,? said a pharmacist. An electrical engineer once sad, ?Reading literary novels? Just wasting time. Such bookd sre just the works daydreamers.? And this is the worst: ?Literature? What kind of animal is it? In our course we have never been taught the definition of that; however I might be able to say that literary works contain complicated ides poured from writer?s mind,? said a student of English Departement of an outstanding university. And I believe it is not too difficult to have many other similar comments.